Philosophy of disciplinary punishment of university faculty in Syria - Almahmoud, Wayel Ahmad; Ake, Walid (Journal of Economic, Administrative and Legal Sciences, 2022)
This research examines the philosophy of disciplinary punishment in terms of the definition of disciplinary punishment, the principles governing it, the types of penalties imposed by the Board of Discipline of Teaching Staff and the manner in which the Board is set up to impose disciplinary punishment on university faculty The main objective of this research is to show the extent to which these disciplinary sanctions contribute to achieving compatibility and a fair balance between the public interest that relates to the proper functioning of the education facility without harming the rights and guarantees of the faculty member in universities, as well as protecting him from the arbitrariness of the administrative authority when signing it. In this study, we followed the analytical approach to study the principles that govern disciplinary penalties and the types of these light penalties imposed by each of the university president, and severe penalties also imposed by the competent disciplinary board stipulated in the Syrian Universities Organization Law. It was concluded that the Syrian Universities Organizing Law specified disciplinary penalties for faculty members exclusively, and the Syrian legislator did not specify disciplinary violations exclusively in the Universities Organizing Law, and did not link each disciplinary violation with the disciplinary punishment ensuing from it, but left the assessment of this to the competent disciplinary authority and we recommend the Syrian legislator Determining a specific disciplinary penalty for each disciplinary violation, in order to protect the faculty member from the arbitrariness of the administrative authority in imposing penalties, although it is difficult to identify all violations, due to their large number and differences.